Association between body roundness index and risks of all-cause and cardiovascular mortality in adults with metabolic dysfunction-associated steatotic liver disease: NHANES 1999–2018 - Yi, Yanshan; Yang, Li (Frontiers in Nutrition, 2025)
BackgroundVisceral obesity is an important risk factor for the development and progression of metabolic dysfunction-associated steatotic liver disease (MASLD). The body roundness index (BRI) is a novel indicator that demonstrates a stronger correlation with visceral fat than other anthropometric indices. However, the association between the BRI and mortality risk in patients with MASLD remains unclear. Therefore, this study investigated the relationship between the BRI and the risks of all-cause and cardiovascular disease mortality among patients with MASLD.MethodsThis study included 7,428 adults aged ≥18 years with MASLD, utilizing data from the National Health and Nutrition Examination Survey (NHANES) database spanning from 1999 to 2018. The assessment of MASLD was conducted based on the fatty liver index (FLI). To examine the relationship between the BRI and mortality risks, multivariable Cox proportional hazards regression models, trend analysis, and restricted cubic spline curves were employed. Additionally, subgroup analyses were conducted to assess whether the association between the BRI and mortality varied across different subgroups.ResultsIn total, 1,249 participant deaths were recorded during a median follow-up period of 115 months, of which 404 were attributed to cardiovascular disease. After adjusting for multiple covariates in the fully adjusted model, the risk of all-cause mortality was increased by 27% (HR: 1.27; 95% CI: 1.00–1.60) and 52% (HR: 1.52; 95% CI: 1.18–1.96) in BRI quartiles 3 to 4 (Q3–Q4) compared with Q1, respectively. Similarly, the risk of cardiovascular disease mortality was increased by 61% (HR, 1.61; 95% CI, 1.05–2.46), 62% (HR, 1.62; 95% CI, 1.03–2.53), and 144% (HR, 2.44; 95% CI, 1.46–4.09) in BRI quartiles 2 to 4 (Q2–Q4) compared with Q1, respectively. The restricted cubic spline curves indicated a linear relationship between the BRI and both all-cause and cardiovascular disease mortality (p for non-linearity >0.05).ConclusionIn this nationally representative sample of adults with MASLD from the non-institutionalized civilian population in the United States, the BRI served as an independent predictor of both all-cause and cardiovascular disease mortality. Specifically, higher BRI values were associated with increased risks of both all-cause and cardiovascular disease mortality among patients with MASLD.